The Effect of Steady Flow on the Physical Quantities of Slow mMagneto Acoustic Waves in Solar Coronal Plasma - Abbas Abedini (Iranian Journal of Astronomy and Astrophysics)
textbf{Damping of slow magnetohydrodynamic(MHD) waves and oscillations are believed to contribute to the heating of the solar corona. Since the launch of solar space telescopes, many observational evidences for the occurrence of slow MHD waves have been detected in various structures of the solar corona.}In this paper, the effect of steady flow of coronal plasma textbf{on the damping time and other physical quantities} of slow magneto-acoustic waves in the presence of thermal conduction and compressive viscosity is studied.The perturbed and linearized MHD Equations of a flowing coronal plasma are solved both analytically and numerically by Mac Cormack method to investigate the effect of steady flows on physical quantities of slow magneto-acoustic waves.The results of this study show that with increasing magnitude values of the Mach number from 0 to 0.6 and increasing the compressive viscosity and thermal conduction coefficient with increasing the temperature from 2 to 6 MK, the oscillation periods, the damping times and the damping qualities change significantly. Also, the results of this study show that the values and limits of the physical quantities calculated for magneto-acoustic waves in a flowing viscous plasma in the presence of thermal conduction at high temperatures (more than 4 MK) correspond to observational values. Moreover, the results indicate that background velocity of the coronal plasma is an effective factor in the damping of slow magneto-acoustic waves.